The endocrine system: Basic science and clinical conditions - Hinson, Joy.; Raven, Peter; Chew, Shern L. (Edinburgh ; New York : Churchill Livingstone/Elsevier, 2010)
An illustrated guide to the endocrine system for medical and health science students that focuses on major diseases, with information on relevant anatomy, physiology, and biochemistry.
Front Cover; The Endocrine System: Basic Science and Clinical Conditions; Copyright Page; Preface; Acknowledgements; Contents; CHAPTER 1 INTRODUCTION; What is endocrinology?; What do hormones do?; Types of hormone: their synthesis and secretion; The transport and metabolism of hormones; Important concepts in endocrine regulation; Endocrine disorders; Endocrine investigations: general principles; CHAPTER 2 RECEPTORS AND HORMONE ACTION; Introduction; General characteristics of receptors; Types of hormone receptors; Cell-membrane receptors; Hormonal regulation of transcription Intracellular receptorsDisorders of receptor function; CHAPTER 3 THE HYPOTHALAMUS AND PITUITARY PART I: THE HYPOTHALAMUS AND POSTERIOR PITUITARY; Introduction; Where can I find the hypothalamus and pituitary?; Connection between the hypothalamus and pituitary; Development of the hypothalamus and pituitary; The hormones of the hypothalamus; The hormones of the posterior pituitary; Release of posterior pituitary hormones is part of a neuroendocrine reflex: oxytocin secretion and actions; Regulation of vasopressin secretion; Actions of arginine vasopressin Disorders of vasopressin secretion and actionThirst; Other hypothalamic hormones; CHAPTER 4 THE HYPOTHALAMUS AND PITUITARY PART II: THE ANTERIOR PITUITARY; Introduction; Structure of the anterior pituitary; The hormones of the anterior pituitary; Regulation of hormone secretion in the anterior pituitary; Growth hormone and prolactin in blood; Actions of the anterior pituitary hormones growth: hormone and prolactin; Disorders of anterior pituitary function: over-secretion; Disorders of under-secretion of anterior pituitary hormones; Tests for hypopituitarism Insufficient growth hormone secretionCHAPTER 5 THE ADRENAL GLANDS PART I: THE ADRENAL MEDULLA; Introduction; Where to find the adrenal glands; Blood supply; Nerve supply; Embryology of the adrenal gland; The adrenal medulla; Disorders of the adrenal medulla: phaeochromocytoma; Familial phaeochromocytoma; Pharmacological uses of hormones of the adrenal medulla; CHAPTER 6 THE ADRENAL GLANDS PART II: THE ADRENAL CORTEX; Introduction; Structure of the adrenal cortex; Hormones produced by the adrenal cortex; Regulation of steroid production; Transport of steroid hormones in blood Disorders of adrenal steroidsPharmacological use of glucocorticoids; CHAPTER 7 THE THYROID GLAND; Introduction; Thyroid anatomy; What is a goitre?; Blood supply; Structure of the thyroid; Synthesis of thyroid hormones; Iodine; Thyroxine and T3: the thyroid hormones in blood; Control of thyroid function; Cellular action of thyroid hormones; Effects of thyroid hormones; Disorders of thyroid hormone secretion; Causes of thyroid hyposecretion; Effects of thyroid hormone insufficiency: myxoedema; CHAPTER 8 HORMONAL CONTROL OF REPRODUCTION PART I: MALE REPRODUCTIVE SYSTEM; Introduction
Includes index.
Keywords: Endocrine glands -- Textbooks; Endocrine glands -- Diseases -- Textbooks; Endocrinology -- Textbooks; Endocrine System -- physiology; Endocrine System Diseases; Hormones